2011
DOI: 10.1002/med.20252
|View full text |Cite
|
Sign up to set email alerts
|

On the selectivity and efficacy of defense peptides with respect to cancer cells

Abstract: Here, we review potential determinants of the anticancer efficacy of innate immune peptides (ACPs) for cancer cells. These determinants include membrane-based factors, such as receptors, phosphatidylserine, sialic acid residues, and sulfated glycans, and peptide-based factors, such as residue composition, sequence length, net charge, hydrophobic arc size, hydrophobicity, and amphiphilicity. Each of these factors may contribute to the anticancer action of ACPs, but no single factor(s) makes an overriding contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(166 citation statements)
references
References 327 publications
(828 reference statements)
7
148
0
1
Order By: Relevance
“…It is generally accepted that the interaction with the CM of target bacteria is an essential step in the antimicrobial action of AMPs [13][14][15][16][17] and interactions of this type have been investigated using a variety of model membranes [18][19][20][21][22][23] . These model membranes are usually formed from lipid mixtures with a head-group composition that reflects the molar ratio of the major lipids in the bacterial membrane, namely PE, phosphatidylglycerol (PG), Lys-PG and cardiolipin (CL).…”
mentioning
confidence: 99%
“…It is generally accepted that the interaction with the CM of target bacteria is an essential step in the antimicrobial action of AMPs [13][14][15][16][17] and interactions of this type have been investigated using a variety of model membranes [18][19][20][21][22][23] . These model membranes are usually formed from lipid mixtures with a head-group composition that reflects the molar ratio of the major lipids in the bacterial membrane, namely PE, phosphatidylglycerol (PG), Lys-PG and cardiolipin (CL).…”
mentioning
confidence: 99%
“…In this conformation, Cn-AMP2 exhibited a strongly hydrophobic region, formed by the C-terminal eight residues of the peptide, YFVFSVGM, which was flanked by a short anionic segment, TES [36,37]. This residue arrangement endows Cn-AMP2 with primary amphiphilicity [36,37], which has been reported for other anticancer peptides such as indolicidin [38,39] and is known to mediate the ability of these peptides to traverse membranes [40]. By analogy to indolicidin, it was suggested that the ability of Cn-AMP2 to traverse cancer cell membranes may be hydrophobicity driven by a mechanism involving the peptide's C-terminal region [36,37].…”
Section: Please Provide Corresponding Author(s) Photograph Size Shoulmentioning
confidence: 86%
“…A structural role has also been suggested for aspartate residues in the case of -helical HDPs such as Cr-ACP1 where they tend to occupy positions that are i ± 3 or i ± 4 relative to basic residues. It has been suggested that this structural positioning may promote helix formation via salt bridging and thereby serve as a strategy to stabilise -helical structure [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews available in the literature provide detailed description of the many different mechanisms underlying cancer cell toxicity (Gaspar et al 2013;Harris et al 2013;Hoskin and Ramamoorthy 2008;Papo and Shai 2005;Mulder et al 2013). Studies on structureactivity relationship have shown that some ACPs share with AMPs the ability to disrupt cell membranes, causing poration or micellization, and additionally inducing necrosis and/or apoptosis (Bhutia and Maiti 2008;Papo and Shai 2005).…”
Section: Mechanisms Of Action Cellular Targets and Selectivity Of Anmentioning
confidence: 99%